BIBLICAL TEXT AND TRANSLATION: THE DIVINE VOICE AT THE HUMAN LEVEL OF COENUNCIATION - Moura Neves, Maria Helena de [UNESP]; Madureira Lopes, Mariu Moreira (Univ Federal Santa Catarina, Nucleo Traducao, 2016)
Currently, biblical text has a multiplicity of versions spread out. These versions go from one pole of literality to the other of liberty in translation. In sight of these facts and of the specificities of biblical text, this paper focuses on the process of coenunciation in order to evaluate how textual-discursive organization is configured in these different versions, aiming at establishing a relation with the intended audience for each of these versions. The comparative analysis between representative versions of each of the poles, having more than one direction of investigation, shows that such relations go from creating effects of great distancing between producer and receptor (typical of literal versions, whose discourse is clothed in injunctive force that demands from the believers the fulfillment of all that is required), to creating effects of a highly marked approximation (typical of free versions, whose discourse seeks to establish a pact with the reader, in an evident relation of cooptation).
Keywords: Coenunciation; Sensitive texts; Biblical translation